Clinical Features and Endovascular Management of Iliac Arteriovenous Fistulas: A 10-Year Single Center Experience - Ji, Lei; Gu, Guangchao; Liu, Zhili; Chen, Yuexin; Ye, Wei; Liu, Bao; Liu, Changwei; Zheng, Yuehong (Frontiers in Surgery, 2022)
Objective: Iliac arteriovenous fistulas (IAVFs) are rare abnormalities with limited reported cases. The present study aimed to summarize the clinical features and experiences on the diagnosis and endovascular treatment of IAVFs. Methods: A single-center retrospective study of IAVFs from 2010 to 2019 was performed. Data including demographics, clinical characteristics, radiological images, surgical details and follow-up were collected. Results: A total of 16 patients diagnosed with IAVFs was identified. The female to male ratio was 3:1. The mean age was 47.7±10.4 (range: 35 to 73) years. Leg swelling and cardiac insufficiency, especially heart failure, were the most common primary symptoms in this series, which were revealed in 68.8% and 37.5% patients respectively. Iatrogenic, traumatic and congenital IAVFs were diagnosed in 62.5%, 12.5% and 25.0% patients, respectively, among which hysterectomy was thought to be the main cause for female iatrogenic IAVFs (31.3%). Anatomic analysis found that internal iliac vessels were the predilected sites of IAVFs. All patients were treated by endovascular procedures composed of transarterial embolization (50.0%), transarterial and stage II transvenous embolization (31.3%), I stage transarterial and transvenous embolization (12.5%), and transarterial embolization plus stent implantation (6.3%). The clinical success rate was 93.8%. Minor complications including fever (18.8%) and exudation at the puncture point (6.25%) were noted and well treated. During a follow-up period of 51.3 ± 41.9 months after operations, only one patient experienced re-emergence of heart failure because of recurrence of leiomyosarcoma, other patients recovered uneventfully with symptoms relief and no severe embolization-related complications was encountered. Conclusion: IAVFs are rare disorders and correct diagnosis requires careful history-taking and physical examination, combined with proper imaging investigation. The primary goal for treatment of IAVFs was to relieve associated symptoms. Based on the results of this study, endovascular approach is safe and effective for treatment of IAVFs.